Research Of Screw Expeller On Oil Palm Seed: A CFD Study On Barrel Zone - Mohamed, Muhammad Aizuddin (Universiti Sains Malaysia, 2018)
The case study was carried out at Kilang Minyak Sawit Kamunting Sdn.Bhd, Taiping. The project research has the aims in finding the relationship between the screw speed and pressure development in a non-intermeshing type of screw expeller. It also interest in finding the relationship of design configuration (different screw pitch length) with the pressure development inside the barrel. The research will be achieved by simulating the barrel zone using the ANSYS Fluent software. Multiple Reference Frame (MRF) technique will be used for the purpose of simulation. As increasing the screw speed, it also increases the pressure development inside the confined space. 40mm and 50 mm screw pitch model will have a higher pressure value and eventually as increasing the screw pitch further on; the pressure value inside the barrel is gradually decreasing. Good agreement was found that the screw speed is directly proportional to the pressure and the throughput of fruit mesh will increase along with it. In axial movement of the fruit mesh (fluid flow), the pressure are gradually decreasing as it moves from the inlet towards the discharge outlet. The mixing behaviour of the double screw expeller is the contributing factor that affects the relationship between screw pitch lengths towards the development of pressure.